Bispectral analysis of broadband turbulence and geodesic acoustic modes in the T-10 tokamak. (11th June 2021) - Riggs, Greg A.; Nogami, S.H.; Koepke, M.E.; Melnikov, A.V.; Eliseev, L.G.; Lysenko, S.E.; Khabanov, P.O.; Drabinskij, M.A.; Kharchev, N.K.; Kozachek, A.S.; Ufimtsev, M.V.
Abstract : Local fluctuations of electrostatic potential, poloidal electric field, magnetic potential and electron density are simultaneously measured in the T-10 tokamak by a heavy ion beam probe (HIBP) having a five-slit energy analyser, which allows an estimate of the turbulent particle flux and E× B rotation velocity in the off-minor-axis gradient zone of the toroidal plasma column. The high spatial and temporal resolution of the modern multichannel HIBP makes it an effective tool to study plasma oscillations. Motivated by previous work that has documented time-resolved interactions between measured plasma parameters using correlation analysis (coherence of E_pol and density n_e, and cross-phase), a new result from bicorrelation analysis (bicoherence of magnetic potential A_ζ and density n_e, and biphase) is reported for documenting the evidence of wave–wave coupling and energy transfer associated with the interaction between geodesic acoustic modes (GAM) and broadband, quasi-coherent modes.